Penerapan Problem Based Learning Berbantuan Lembar Kerja Peserta Didik untuk Meningkatkan Keterampilan Berpikir Kritis Siswa - Masnah Masnah; Siti Nurhidayati; Ida Royani (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study was motivated by the low critical thinking skills of Grade XI students at SMA Negeri 11 Mataram during biology lessons, evidenced by a lack of active participation and learning outcomes that failed to meet the Minimum Mastery Criteria (KKM) of 75. This situation stemmed from instruction that remained teacher-centered and did not foster higher-order thinking skills. The study aimed to enhance students' critical thinking skills by implementing the Problem-Based Learning (PBL) model supported by Student Worksheets (LKPD) for the topic of the reproductive system. This research was a Classroom Action Research (CAR) study conducted over two cycles each comprising planning, implementation, observation, and reflection stages involving 17 Grade XI students at SMA Negeri 11 Mataram. Data were collected using essay tests based on critical thinking indicators and observation sheets regarding the implementation of instruction. The data were analyzed using descriptive quantitative methods. The results showed that the students' average critical thinking score rose from 49 in Cycle I to 77 in Cycle II, while the percentage of learning mastery increased from 35.2% to 88.2%. Based on these findings, it is concluded that the implementation of the PBL model supported by LKPD can improve students' critical thinking skills in biology learning.